Benomyl treatment decreases fecundity of ant queens - Pech, Pavel; Heneberg, Petr (Journal of invertebrate pathology, 2015)
Methyl benzimidazole carbamate fungicides, including benomyl, are widely used in agriculture, and to eliminate entomopathogenic infections. We treated queens of Myrmica rubra (Hymenoptera:Formicidae) infected or not by Rickia wasmannii (Laboulbeniales:Laboulbeniaceae) with benomyl, 1mg/ml p.o. for six weeks. Benomyl did not treat the infection, and the treatment alone caused strong decrease in the fecundity of control healthy queens from 18.0±8.4 to 3.7±5.2eggs per healthy queen. This is the first evidence on severe adverse effects of methyl benzimidazole carbamate fungicide on the fecundity of insects, which might be responsible for altered species composition of ant assemblages in the cultural landscape.
Keywords: fertilita; Animals; Methyl 1-(butylcarbamoyl)benzimidazol-2-yl-carbamate; Population dynamics; průmyslové fungicidy; Ants; Female; Benlate; Environmental chemicals; Fungicides, Industrial; zvířata; Carbendazim; Microgyne; Benomyl; benomyl; Fertility; ženské pohlaví; Formicidae